Factors Related to the Incidence of Diarrhea among Toddlers - Hilky Ofan; Rusni Safitry; Suherman Suherman B (Inspirasi Foundation, 2024)
Objective: The purpose of this study was to determine the factors related to the incidence of diarrhea in toddlers at Tinambung Health Center. Method: namely cross sectional. The sampling method was Purposive sampling, the number of samples was 85 toddlers. Result: Statistical Test using Chi Square test formula to determine factors related to diarrhea incidence, it was found that there is a relationship between knowledge about diarrhea, behavior and consumption of boiled water with diarrhea incidence in toddlers where all factors have p value = 0.000 (p <0.05), meaning that there is a relationship between knowledge about diarrhea, behavior and consumption of boiled water with diarrhea incidence in toddlers. Conclusion: This study shows a relationship between maternal knowledge, maternal behavior and water consumption in cooking with the incidence of diarrhea in toddlers in the Tinambung Health Center work area with a significant level of p = 0.000 for all variables.